Hepatitis B virus transactivator X protein is not tumorigenic in transgenic mice. - Lee, T H (1990)
The hepatitis B virus X protein acts as a transcriptional transactivator in vitro. To elucidate possible biological effects of X protein on liver cells in vivo, we generated four lines of transgenic mice carrying the X gene open reading frame under the control of the human alpha-1-antitrypsin regulatory region. The plasmid construct used to introduce the transgene was shown to encode a 16-kDa X protein with transactivating capability. The expression of X protein was detectable in liver tissue of transgenic animals of three of the lines by immunoblot analysis; levels of expression were highest in the first month after birth of the animals. Over 80 animals from the expressing lines were examined histologically. Most transgenic mice, some of which were observed for up to 2 years, remained normal. However, a few transgenic animals developed mild focal hepatitis, nuclear pleomorphism, focal necrosis, and/or nodular hyperplasia in the liver. Increased mitotic activity of hepatocytes also was observed. We conclude that, at the level of expression achieved in these transgenic mice, the hepatitis B virus transcriptional transactivator X protein alone does not appear to mediate the development of serious liver damage or hepatocellular carcinomas.